The school to prison pipeline : the role of culture and discipline in school - Okilwa, Nathern; Khalifa, Muhammad A., 1975-; Briscoe, Felecia (Bingley, U.K. : Emerald Publishing Limited, 2017)
This edited volume focuses on the role that school climate and disciplinary practices have on the educational and social experiences of students of color. Drawing from quantitative, qualitative, and theoretical studies, it brings to bear a number of topics such as racialized school experiences; criminology, discursive deviance and punishment and carceral studies; urban studies; school administration and leadership; and, a number of critical theorist frameworks. Practical insights are offered to assist administrators, teachers, school counsellors, and other school and non-school based professionals on how to address not only disparities in school discipline, but also create and promote an inclusive, affirming positive school culture and climate. With applications in disciplinary studies and criminology, leadership studies, critical race theory and other critical frameworks, this volume is a valuable resource advancing new theoretical concepts.
Prelims -- Introduction and overview -- The indignities on which the school-to-prison pipeline is built: life stories of two formerly incarcerated black male school-leavers -- Resisting the school-to-prison pipeline utilizing guidance from the frontlines: Chicano student experiences as a source of knowledge and strength -- Discipline and punishment: how schools are building the school-to-prison pipeline -- Pathologizing the White'unteachable': south London's working-class boys experiences with schooling and discipline --'What are we restoring?' Black teachers on restorative discipline -- Can PBIS build justice rather than merely restore order? -- A systems theory analysis for ending the school-to-prison pipeline: using disability rights laws to keep children in schools and out of courts, jails, and prisons -- What we can do right now: what needs further research? -- About the editors and contributors -- Index.
Includes bibliographical references.
Keywords: Education -- Multicultural Education; Education; Juvenile deliquency -- prevention; Problem youth -- Education; Culturally relevant pedagogy